Politik Identitas dan Multikulturalisme : The Gods Must be Crazy II (1989) - yati, Mulyati; Hellen Permatasari; Dini Otafiana; Tini Haryani; Aswandi; Alif Farhan Habibie; Marlina; Kustiawan (Jurnalika : Jurnal Ilmu Komunikasi, 2024)
The aim of this research is to find out what happens to identity politics and multiculturalism in the film "AND MULTIUCULTURALISM IN THE FILM "THE GODS MUST BE CRAZY II" (1989). In this research the author uses a qualitative approach method. In this research, the author collected data by studying literature from journals, articles and films. The analysis technique used is qualitative descriptive. The film "The Gods Must Be Crazy II" (1989) is a comedy film originating from South Africa. Even though this film focuses more on comedy elements, there is a background of identity politics and multiculturalism that can be found in the context of this film. Identity politics relates to how individuals or groups identify themselves based on characteristics such as ethnicity, religion, language, or culture. Overall, "The Gods Must Be Crazy II" (1989) uses a comedic approach to highlight the complexity of relationships between different ethnic groups. different in South Africa.